Coming to stay or to go? Stay intention and involved uncertainty of international students - Fabian Koenings; Tina Haussen; Stefan Toepfer; Silke Uebelmesser (Journal of Regional Science, 2021)
Countries compete for young talents to alleviate skilled-labor shortage. International students, who stay after graduation, allow host countries to overcome this challenge. This study investigates the factors associated with international students' intention to stay or to go after graduation from a host country's perspective. In contrast to the literature, this analysis employs survey data collected from first-semester students. This assures that the analysis is not distorted by attrition. Furthermore, it allows policymakers to address those students who would be no longer around later in the absence of any policy measure. At the same time, it requires to deal with uncertainty as the actual migration decision will be later. This study introduces a set of uncertainty models to the migration context. The results show that, next to career opportunities and a stay in the host country before the studies, being enrolled in a Bachelor program instead of a Master program is significantly associated with the intention to stay. The findings are largely robust to different approaches accounting for the uncertainty involved. Further, Master students are found to be significantly more uncertain than Bachelor students.
Keywords: 320; international students; labor shortage; stay intention; uncertainty